Dietary Fibers - Waisundara, Viduranga Y. (IntechOpen, 2022)
Dietary fibers have been identified as a food ingredient of importance due to their ability to act on the gut microbiome. The health benefits of dietary fibers have been numerous and not just limited to this alone. Since time immemorial, dietary fibers are identified as playing a significant role in the normalization of bowel movements and also helping control blood glucose and cholesterol levels, as well as control weight gain. The book provides fundamental knowledge on dietary fibers as well as shares insights and updates on their health benefits. The chapters have been written by experts in these two areas and it is hoped that the profits from going through the content are substantial